Immunoglobulin free light chains and interleukin-6 levels in prediction of kidney injury in patients with multiple myeloma - Aganovic-Musinovic, Izeta; Avdagic, Nesina; Babic, Nermina; Zaciragic, Asja; Lepara, Orhan; Huskic, Jasminko; Todic-Rakanovic, Maida (Asian Journal of Medical Sciences, 2019)
Background: Multiple myeloma (MM) is a disease of B cell population with excessive secretion of immunoglobulins and presence of free light chains (FLCs) that are by products of immunoglobulin synthesis. Free light chains play crucial role in causing renal damage. Interleukine-6 (IL-6) supports the survival and/or expansion of MM cells by stimulating cells as well as by preventing programmed cell death. Aims and Objectives: The aim of this study was to evaluate serum and urine free light chains (FLC)measurement and compare with IL-6 levels in patients with different stages of Multiple Myeloma (MM) and control group of subjects and to determine their relevance in acute kidney injury occurrence. Materials and Methods: Recruitment of patients with MM (n=62) made the hematologist that followed clinical Solomon-Durie MM classification. Control group consisted of 20 healthy individuals. Results: Patients with MM and renal function injury had significantly higher concentration of urine κ chains compared to control group and group of MM without renal function injury (p<0.005), whereas this difference was not observed when the patients were divided into disease stages groups. Concentration of IL-6 was significantly higher in patients at MM steady stage compared to control group (p<0.001) and significant difference was also detected in patients with MM at relapse stage and control group (p<0.0005). Concentration of IL-6 in MM patients without renal function and with renal function injury was significantly higher compared to control group (p< 0.001; p<0.0005 respectively). Statistically significant correlation was determined between sera κ and urine κ chains (rho=0.437; p<0.01) as well as between urine λ and sera λ chains (rho=0.505; p<0.01) and between urine κ and urine λ chains (rho=0.364; p<0.01). Conclusion: Results showed that urine κ chains, sera κ chains and IL-6 are constructing a fine tuned net and point to conclusion that FLC and IL-6 are important for an early treatment response detection for patients with potentially reversible renal failure.